MANAGEMENT OF LEARNING IN ARTS AND DESIGN CREATION BASED ON DIGITAL MEDIA FOR THE MILLENIAL GENERATION - Sustiawati, Ni Luh; Sari, Ni Luh Desi In Diana; Dewi, Ni Luh Ayu Cempaka (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
The millennial generation, born and raised during the era of information technology development, has learning the characteristics that tend to be interactive, visual, flexible, and closely tied to the use of digital technology. Millennials are more likely to understand material through media such as graphic elements, videos, or interactive simulations, which allow them to learn both independently and collaboratively in various situations. Additionally, the flexibility of time and place in accessing learning through digital devices is a major advantage that supports their learning patterns. These characteristics demand an innovative, adaptive, and technology-based educational approach to enhance learning motivation and optimize their creative and innovative potential. This study examines the management of learning in arts and design creation based on digital media for the millennial generation. A qualitative approach was used, collecting data through interviews, observations, and documentation, then analyzed descriptively to identify relevant patterns and strategies. This study is expected to contribute to optimizing the potential of the millennial generation and promoting innovation in technology-based education.